Distinct Psychological Characteristics Predict Resilience and Recovery Throughout Widowhood. Issue 3 (May 2022) - Rackoff, Gavin N.; Newman, Michelle G.
Highlights: Death acceptance predicted less increase in depression during early widowhood. Death acceptance predicted less decline in depression during later widowhood. Perceived control predicted greater decline in depression during later widowhood. Death acceptance and perceived control could serve unique protective roles. Abstract: The dual-process model proposes that early and later bereavement involves different types of stressors and adaptation processes (Stroebe & Schut, 1999, 2010). It is thus possible that different factors facilitate adaptation during the early months versus subsequent years following widowhood. Elevated depressive symptoms, though prevalent after widowhood, may indicate problematic adaptation, as they are associated with poor long-term physical and mental health outcomes. We predicted that neutral death acceptance would be associated with less increase in depression during early widowhood (when confronted with loss-oriented stressors), whereas perceived control would predict depressive symptom decline during later widowhood (when adapting to controllable restoration-oriented stressors). Older adults ( N = 265) reported on neutral death acceptance, perceived control, and depression before widowhood and on depression 0.5, 1.5, and 4.0 years after the death of their spouse. Bilinear spline growth modeling revealed that, on average, depressive symptoms increased from before to 0.5 years after spouse death and fell from 0.5 to 4.0 years after spouse death. Neutral death acceptance predicted a smaller increase in depression from before to 0.5 years after spouse death, as well as a smaller subsequent decrease in depression from 0.5 to 4.0 years after spouse death. Perceived control predicted a larger decrease in depression from 0.5 to 4.0 years after spouse death. Neutral death acceptance and perceived control had unique associations with resilience and recovery throughout early and later widowhood. These variables may be fruitful targets in interventions for depression throughout the full course of widowhood.